The Role of High-Resolution Ultrasound in the Assessment of Surgical Candidates for Transoral Endoscopic Thyroidectomy Via Vestibular Approach (TOETVA) - Beatriz Rebelo; Ricardo Nogueira; Mariana Horta (Acta Médica Portuguesa, 2023)
The approach of surgical techniques has evolved significantly over the last decade, with natural orifice surgeries replacing traditional open approaches. In 2016, Angkoon Anuwong, in Thailand, demonstrated it was possible to perform thyroidectomies in a series of patients by a transoral endoscopic ap-proach – transoral endoscopy thyroidectomy vestibular approach (TOETVA) – with similar complication rates when compared to conventional surgeries. This transoral surgery has become a safe alternative with better cosmetic results, compared to conventional open-route procedures, like Kocher cervi-cotomy. Indeed, it is an option to surgically treat neoplastic and functional thyroid diseases. The technique is performed through a median incision in the oral vestibule, plus two bilateral incisions, followed by the insertion of three trocars, one centrally for a camera, and two laterally for working instruments. Although revolutionary, TOETVA has its technical limitations. Therefore, it is important to precisely define the preoperative eligibility criteria for this type of surgical approach. High-resolution ultrasound is the first imaging modality for the assessment of thyroid nodules, lymph node metastases and surgical field. The aim of this article is to outline the sonographic technique and the role of high-resolution ultrasound in the presurgical evaluation of TOETVA.